Self-perspective Versus Caregiver-perspective on Cognitive Impairment at Different Stages of the Alzheimer's Continuum - Seckin, Mustafa; Ozturk, Gulcan; Dilmac, Ecem; Gurvit, Hakan (GALENOS PUBL HOUSE, 2022)
Objective: To understand how the patients' and their study partners'/caregivers' perspectives on cognitive decline change at the subjective cognitive decline (SCD), mild cognitive impairment (MCI), and probable Alzheimer's disease (PRAD) stages of the Alzheimer's disease (AD) continuum. Materials and Methods: Twenty-three individuals with the diagnosis of SCD, 33 individuals with the diagnosis of MCI, and 17 individuals with the diagnosis of PRAD were included. A cognitive testing battery including the standardized mini-mental state examination (MMSE), digit span forward and backwards tests, and the semantic fluency test were administered to all patients. The cognitive function instrument (CFI) was used for the subjective assessment of cognitive decline. The same questions in the CFI were answered both by the patients (CFI-self report) and the study partners (CFI-partner report). Results: In the SCD and the MCI groups, the CFI-self report scores were higher than the CFI-partner report scores, whereas an opposite pattern was found in the PRAD group with higher CFI-partner report scores and lower CFI-self report scores. The CFI self report scores positively correlated with the MMSE scores in the PRAD group showing higher ratings in cognitively less impaired individuals, and vice versa. The CFI partner-report scores did not show a significant correlation with the MMSE scores in any of the groups, however a trend for a negative correlation was observed in the MCI group. Finally, the CFI-self report and partner report scores significantly correlated only in the MCI group. Conclusion: Report-based assessment of cognitive decline can be informative, particularly in the early stages of the AD continuum. However, the loss of insight in PRAD may mask the symptoms when the subjective cognitive assessment relies on the patients' perspective. The greatest concordance between the patients' and their partners' perspectives was evident in the MCI stage which represented a transitional period between SCD and PRAD.
Keywords: Cognitive function instrument; Turkish; subjective cognitive decline; mild cognitive impairment; Alzheimer's disease